ROLE OF FLUID IN THE GENESIS OF CARBONATITES AND ALKALINE ROCKS: GEOCHEMICAL EVIDENCE - Rass I.T.; Abramov S.S.; Kozlovskii V.M.; Korpechkov D.I.; Utenkov V.A. (My University, 2006)
In most alkaline-ultrabasic-carbonatite ring complexes, the distribution of trace elements in the successive derivatives of mantle magmas is usually controlled by the Rayleigh equation of fractional crystallization in accordance with their partition coefficients, whereas, that of late derivatives, nepheline syenites and carbonatites, is usually consistent with trends characteristic of silicate-carbonate liquid immiscibility. In contrast to the carbonatites of ring complexes, carbonatites from deep-seated linear zones have no genetic relation with alkaline-ultrabasic magmatism, and the associated alkaline rocks are represented only by the nepheline syenite eutectic association. The geochemical study of magmatic rocks from the Vishnevye Gory nepheline syenite-carbonatite complex (Urals), which is assigned to the association of deep-seated linear zones, showed that neither differentiation of a parental melt nor liquid immiscibility could produce the observed trace element distribution (Sr, Rb, REE, and Nb) in miaskites and carbonatites. Judging from the available fragmentary experimental data, the distribution patterns can be regarded as possible indicators of element fractionation between alkaline carbonate fluid and alkaline melt. Such trace element distribution is presumably controlled by a fluid-melt interaction; it was also observed in carbonatites and alkaline rocks of some ring complexes, and its scarcity can be explained by the lower density of aqueous fluid released from magma at shallower depths. © Pleiades Publishing, Inc. 2006.